Public Health Forum : Forschung - Lehre - Praxis (De Gruyter, 1993)
Public Health Forum deals with the preservation and promotion of health and the question on how diseases can be prevented and overcome. The Journal reports on the individual conditions and social context, and the possibilities and limits for promoting health, and preventing and controling disease in light of management-relevant questions, and ethically and economically acceptable measures.